Virtual surgery in a (tele-)radiology framework - Glombitza, Gerald; Evers, Harald; Haßfeld, Stefan; Engelmann, Uwe; Meinzer, Hans-Peter (IEEE transactions on information technology in biomedicine, 1999)
Presents telemedicine as an extension of a teleradiology framework through tools for virtual surgery. To classify the described methods and applications, the research field of virtual reality (VR) is broadly reviewed. Differences with respect to technical equipment, methodological requirements and areas of application are pointed out. VR, desktop VR and augmented reality are differentiated and discussed in some typical contexts of diagnostic support, surgical planning, therapeutic procedures, simulation and training. Visualization techniques are compared as a prerequisite for VR and assigned to distinct levels of immersion. The advantage of a hybrid visualization kernel is emphasized with respect to the desktop VR applications that are subsequently shown. Moreover, software design aspects are considered by outlining functional openness in the architecture of the host system. A teleradiology workstation was extended by dedicated tools for surgical planning through a plug-in mechanism. Examples of recent areas of application are introduced, such as liver tumor resection planning, diagnostic support in heart surgery, and craniofacial surgery planning. In the future, surgical planning systems will become more important. They will benefit from improvements in image acquisition and communication, new image processing approaches and techniques for data presentation. This will facilitate pre-operative planning and intra-operative applications.
Gesehen am 22.02.2021